The challenge of designing culturally - Jahn Kassim, Puteri Shireen (BCI Asia, 2018)
In his seminal book “Leaves of the Same Tree: Trade and Ethnicity in the Straits of Melaka”, Professor Leonard Andaya paints a picture that reaches out in time, beyond the confines of the present geographical boundaries of nations. The memory of lands bordering the Straits of Melaka—known as lands within the Sea of ‘Malayu’—were rich and ‘rhizomic’ in expression, filled with multicultural crisscrossing of forces. For centuries, this Southeast Asian region was a dynamically-charged field in which traders from China, India and the Middle East met and exchanged goods, services and cultural ideas. Each ethnicity, race and group had their role and place, yet they were able to sustain their own identity amid a system of mutual benefits.